Ethylene response factor AcERF91 affects ascorbate metabolism via regulation of GDP-galactose phosphorylase encoding gene (AcGGP3) in kiwifruit. (December 2021) - Chen, Yuan; Shu, Peng; Wang, Ruochen; Du, Xiaofei; Xie, Yue; Du, Kui; Deng, Heng; Li, Mingzhang; Zhang, Yang; Grierson, Don; Liu, Mingchun
Highlights: Ascorbic acid (AsA) content is decreased during developmental and ripening stages of kiwifruits. AcGGP is a key enzyme of AsA metabolism in kiwifruit. Overexpression of AcERF91 in kiwifruit significantly increased the AsA content. AcERF91 regulates AsA metabolism by binding to the promoter of AcGGP3 . Abstract: Kiwifruit is known as 'the king of vitamin C' because of the high content of ascorbic acid (AsA) in the fruit. Deciphering the regulatory network and identification of the key regulators mediating AsA biosynthesis is vital for fruit nutrition and quality improvement. To date, however, the key transcription factors regulating AsA metabolism during kiwifruit developmental and ripening processes remains largely unknown. Here, we generated a putative transcriptional regulatory network mediating ascorbate metabolism by transcriptome co-expression analysis. Further studies identified an ethylene response factor AcERF91 from this regulatory network, which is highly co-expressed with a GDP-galactose phosphorylase encoding gene ( AcGGP3 ) during fruit developmental and ripening processes. Through dual-luciferase reporter and yeast one-hybrid assays, it was shown that AcERF91 is able to bind and directly activate the activity of the AcGGP3 promoter. Furthermore, transient expression of AcERF91 in kiwifruit fruits resulted in a significant increase in AsA content and AcGGP3 transcript level, indicating a positive role of AcERF91 in controlling AsA accumulation via regulation of the expression of AcGGP3 . Overall, our results provide a new insight into the regulation of AsA metabolism in kiwifruit.